Fiscal Resources of Local Self – Government Budgets from Environmental Charges on Czech Republic (Lex localis - Journal of Local Self-Government, 2017)
Protection and creation of environment represents a significant problem in Czech society - at the state and local governments. The state, regions and municipalities are responsible for creating and maintaining a healthy environment for their citizens and for future generations. Economic development brings the raising of living standards on one side, however, presents on the other side many negative moments resulting from the creation of environmental burdens of various kinds, in particular, the territory exploitation by mining activities, water and air pollution and industrial and municipal waste disposal. The state imposes taxes and charges on originators of environmental burdens, whose revenue is then used to finance programs and projects for the rehabilitation of the environment and its gradual improvement. This article is the outline of these payments catalog.